Communication for Social Change: Empowering Marginalized Communities through Participatory Media - Nurjaya, Nurjaya; Nahria, Nahria; Hasrul, Hasrul; Levi, Syamsuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the role of Communication for Social Change in empowering marginalized communities through participatory media. In the context of increasingly complex social inequality, participatory communication is seen as an effective strategy to increase critical awareness, strengthen community capacity, and foster inclusive social transformation. This study uses a qualitative approach with a case study method on marginalized communities that actively utilize participatory media such as community radio, local digital platforms, and social media. Data was obtained through in-depth interviews, participatory observation, and community media content analysis. The results show that active community involvement in the communication process can strengthen their bargaining position in public decision-making, expand advocacy networks, and create an equal space for dialogue between communities and stakeholders. In addition, participatory media serves as a catalyst in building collective identity, fighting for social rights, and accelerating sustainable social change. These findings confirm that communication for social change has strategic potential in realizing social justice, strengthening participatory democracy, and empowering marginalized communities.